Helicobacter pylori: recent advances in the study of its pathogenicity and prevention Helicobacter pylori: avances recientes en el estudio de su prevención y patogenicidad - Germán R. Aguilar; Guadalupe Ayala; Geny Fierros-Zárate (Instituto Nacional de Salud Pública, 2001)
Helicobacter pylori has acquired great importance during the last two decades, after being recognized as an important pathogen that infects a great portion of the human population. This microorganism is recognized as the main causal agent of chronic gastritis and duodenal ulcers, and it is associated with the subsequent development of gastric carcinoma. The pathogenic mechanisms of H. pylori and their relation to gastric ailments have not been clearly defined. However, at present it is well established that urease, vacuolating cytotoxin VacA, and the pathogenicity island (cag PAI) gene products, are the main factors of virulence of this organism. Thus, individuals infected with strains that express these virulence factors probably develop a severe local inflammation that may induce the development of peptic ulcer and gastric cancer. The way the infection spreads throughout the world suggests the possibility that there are multiple pathways of transmission. Due to the importance that H. pylori has acquired as a human pathogen, laboratories worldwide are attempting to develop a vaccine that confers long-term immunological protection against infection by this microorganism. Hence, the objective of this review is to present the most relevant findings of the biology of H. Pylori and its interaction with the human host. The full version of this paper is available too at: http://www.insp.mx/salud/index.html Helicobacter pylori ha adquirido gran importancia durante las últimas dos décadas, al ser reconocido como un importante patógeno que infecta una gran porción de la población humana. Este microrganismo es reconocido como el principal agente que causa la gastritis crónica y la úlcera duodenal, además de que se ha asociado con el subsecuente desarrollo del carcinoma gástrico. Los mecanismos patogénicos de H. pylori y su relación con los padecimientos gástricos no se han definido en forma clara. Sin embargo, actualmente está bien establecido que la ureasa, la citotoxina vacuolizante VacA y los productos de los genes de la isla de patogenicidad (cag PAI) son los principales factores de virulencia de este organismo. Así, los individuos infectados con cepas que expresan dichos factores de virulencia, probablemente manifiesten una marcada inflamación local que podría inducir el desarrollo de úlcera péptica y cáncer gástrico. La manera como la infección se propaga a nivel mundial sugiere la posibilidad de múltiples vías de transmisión. A consecuencia de la importancia que H. pylori ha adquirido como patógeno humano, los laboratorios del mundo se esfuerzan para desarrollar una vacuna que confiera protección inmunológica de larga duración contra la infección por este microorganismo. El objetivo de esta revisión es presentar los hallazgos más relevantes sobre la biología de H. pylori y su interacción con su huésped humano. El texto completo de este artículo también está disponible en: http://www.insp.mx/salud/index.html